YOUTUBE AS A MEDIA FOR STUDENTS’ COMPREHENSIVE LISTENING ABILITY AT JUNIOR HIGH SCHOOLS IN BEKASI - Sigit Widiyarto; Mulyadi; Lusiana Wulansari; Aster Pujaning Ati (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
Learning in the listening aspect is still challenging for middle and upper level students due to weak vocabulary, structure, and speaking skills, and many students often struggle with comprehensive listening. This study aimed to determine the increase in learning outcomes after utilizing YouTube as a learning media, measure the impact, and describe the learning process using YouTube media. The study used an experimental method with pretest and posttest only, involving 35 students of class VI SMP Alikhlas Bekasi. Data were collected from tests before and after treatment using YouTube media, processed with SPSS 20, and tested for normality and homogeneity before using a paired sample test. The results showed an increase of 12.2941, indicating that YouTube improved listening skills. Utilizing YouTube included searching for material, watching and listening to the content, analyzing, and distributing it to students and teachers. It is recommended that teachers provide sufficient time and opportunities for students to develop their abilities independently through YouTube, with consistent evaluation and supervision as the key to successful learning.